Performance of crop sequences on coarse-textured soil under rainfed condition - SINGH, RANJODH; VERMA, H N; GILL, M S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1984-90 to study the performance of different crop sequences on coarse-textured soils of Hoshiarpur under rainfed condition. The crop sequences were greengram (Phaseolus radiatus L.). green-manure sunnhemp (Crotalaria juncea L.) and fallow during the rainy season, and wheat (Triticum aestivum L. emend. Fiori & Paol.), wheat + gram (Cicer arietinumL.)mixture and indian mustard [Brassica juncea (L.) Czernj. & Cosson] during the winter season. In the years of normal distribution of seasonal rainfall, sunnhemp-wheat or wheat + gram gave good yield. Under adequate seeding-zone moisture and well-distributed winter rain, green-manuring with sunnhemp-wheat sequence gave the maximulo yield. However, monetary retum of greengram-indian mustard was the maximum. Among the winter-season crops tried, indian mustard gave maximum economic return, greater stability of yield and less chance of crop failure due to severe drought.